Meningkatkan Hasil Belajar Matematika Siswa Menggunakan Model PBL Terintegrasi Pembelajaran Berdiferensiasi Dan Pembelajaran Sosial Emosional - Annissabrina, Imelsi; Sofwan, Muhammad; Iskandar, Dedi; Wahyuni, Ida (Trapsila: Jurnal Pendidikan Dasar, 2024)
This research was motivated by the low mathematics learning outcomes of fourth-grade students at SD Negeri 19/IV Jambi. The aim of this study is to improve students’ mathematics learning outcomes by using a problem-based learning (PBL) model integrated with differentiated and social-emotional learning. The research method employed was classroom action research focused on improving the quality of the learning process by following these steps: (1) planning, (2) action implementation, (3) observation, and (4) reflection. Data collection techniques used were observation and written tests with rubric instruments, multiple-choice, and short answer questions. The data analysis technique used was descriptive qualitative and quantitative data analysis. The results of this study indicate an improvement in students’ learning outcomes after the application of the problem-based learning model integrated with differentiated and social-emotional learning. The average pre-cycle learning outcome score was only 56.19 with a learning objective achievement percentage of 28.57%, while in cycle I after the intervention, the average learning outcome score was 71.9 with a learning objective achievement percentage of 66.66%, and in cycle II there was an increase in the average learning outcome score to 80, with a learning objective achievement percentage of 90.47%. The conclusion of this study is that the implementation of the problem-based learning model integrated with differentiated and social-emotional learning can improve the mathematics learning outcomes of fourth-grade students.